Megaloblastic anaemia due to sulphasalazine responding to drug withdrawal alone. Issue 726 (April 1986) - Grieco, A.; Caputo, S.; Bertoli, A.; Caradonna, P.; Greco, A. V.
Abstract : A 60 year old man with ulcerative colitis since 1975 and treated with sulphasalazine, presented with severe megaloblastic anaemia caused by folate deficiency. The drug was stopped, and the anaemia recovered promptly. There was no relapse one year later.